Regionalized Discount Rate to Evaluate Renewable Energy Projects in Colombia - MarÃn, Jorge Barrientos; Villada, Fernando (International Journal of Energy Economics and Policy, 2020)
In this paper we are interested in estimating the discount rate for electricity generation projects using renewable resources. More precisely we estimate the weighted average cost of capital (WACC). One of the most important feature of this research is that our WACC must be differentiated by regions, which is a challenging purpose taking into account that Colombia is a country with many regions that greatly differ among themselves. This goal requires estimating a risk parameter for each region, in this case for each state of the country, which would have the immediate effect of regionalizing the WACC for renewables non-conventional generation energy projects. it is worth noting that the emerging market bond index (EMBI+) is not a useful measurement of risk at regional level, so we have to look for a variables set in order to capture that risk. We propose to consider variables associated with corruption and violence levels in each state of the country in order to identify regional WACC. Keywords: electricity generation, renewable energy resources, weighted average cost of capital, country and regional risk. JEL Classifications: C21, G11, G12, G18, Q33, Q42 DOI: https://doi.org/10.32479/ijeep.8924